Kinematic and plantar pressure analysis in Strumpell-Lorrain disease: A case report - Roberto Tedeschi (Brain Disorders, 2023)
Background: Hereditary Spastic Paraparesis (HSP), also known as Strumpell-Lorrain disease, is a neurodegenerative disorder characterized by progressive muscle weakness, lower limb spasticity, and abnormal gait. It is a genetically inherited condition affecting the spinal cord. Currently, there is a lack of scientific literature on the evaluation of space-time parameters and plantar pressures in individuals with HSP. Therefore, the objective of this study is to assess spatial-temporal parameters and plantar pressures using motion sensors and a baropodometric platform. Case presentation: A 50-year-old female patient with a body mass index (BMI) of 22.28 presented to our hospital with a 12-year history of Strumpell-Lorrain disease. She exhibited typical symptoms of the disease, including spastic paraparesis in the lower limbs, leading to difficulty in walking. The initial symptom of difficulty walking was diagnosed when she was 38 years old. Apart from walking impairments associated with spasticity and ataxia, the patient demonstrated paraparesis and weakness in the lower limbs, without any cognitive deficits. Conclusions: This analysis elucidates the challenges faced by the patient with Strumpell-Lorrain disease in walking, particularly during the swing phase, resulting in a reliance on monopodal support. Additionally, the patient experiences difficulty in dorsiflexion of the ankle due to spasticity in the gastrocnemius muscle, leading to an increased load on the forefoot. These findings contribute to a better understanding of the specific gait abnormalities and biomechanical impairments associated with Strumpell-Lorrain disease.